Changes in the Number of Medal Events, Sport Events, and Classes During the Paralympic Games: A Historical Overview - Baumgart, Julia Kathrin; Blaauw, Eline Renee; Mulder, Roy; Severin, Anna Cecilia (Frontiers in Sports and Active Living, 2022)
Purpose: To chart how changes in the number of medal events relate to changes in the number of sport events and classes during the Paralympic Games (PG) between 1960 and 2018. Methods: Web-scraping was used to extract information from the website of the International Paralympic Committee on all unique medal events, sport events, and classes per PG, which were then accumulated per sport to descriptively identify and further explore changes. Results: The increased number of medal events during the early Summer Games (SG) (1960-1984: 113-975) and Winter Games (WG) (1976-1994: 55-113) was primarily due to an increased number of classes and sport events. While this suggested an increased sports participation among athletes with disabilities, it made the PG difficult to organise. A decrease in the number of medal events subsequently occurred during the SG (1984-1992: 975-489) and WG (1994-2006: 133-58). This was mainly achieved by reducing the number of sport events in the larger sports. Following this decline phase, the number of medal events and sport events has remained relatively stable for both editions of the PG, though this was achieved through different strategies. The WG employed the time-factor system for all individual sports, which enabled competitions across classes within sport events and thus, awards a single gold medal (one medal event) for several classes. The SG have maintained the number of medal events despite a slight increase in classes (112-181). This was due to some sports combining classes in the same event, while others excluded certain classes from certain sport events. Conclusions: The number of medal events during each PG appear to be closely related to the number of sport events and, partially, to the number of classes. The stability in the number of medal events may indicate that a balance has been achieved, where there currently are enough classes and sport events to ensure fairness, while also maintaining a level of prestigiousness for winning a medal. However, whether this stability will last or if the continued growth of the PG with more athletes and countries will warrant changes in the number of medal events remains to be seen.